Protein Intake, Dietary Diversity, and Length-for-Age Nutritional Status Among Children Aged 6-23 Months: A Comprehensive Overview Study - Laksmi Trisasmita; Alda Erica Lande Randabunga (Journal of Global Nutrition, 2025)
Breastfeeding fulfills the nutritional needs of infants aged 0-6 months. However, after six months, the nutritional requirements increase, necessitating the introduction of complementary foods (CF) rich in diverse protein sources, including animal and plant proteins, to support child growth. This study aims to describe the intake of animal and plant proteins, dietary diversity, and nutritional status (length-for-age) among children aged 6-23 months in the Maros Baru Public Health Center area. A descriptive quantitative study with a cross-sectional design was conducted, involving 171 children aged 6-23 months selected using multistage simple random sampling. Nutrient intake was assessed through a 24-hour food recall questionnaire, and dietary diversity was evaluated using the Minimum Dietary Diversity for Children (MDDC) questionnaire. Results showed that 42.7% of children were stunted. The daily total protein intake of stunted children (15.80 g) was lower than that of non-stunted children (19.65 g). Daily animal protein intake was also lower in stunted children (11.10 g) compared to non-stunted children (17.15 g), while plant protein intake was higher in stunted children (2.30 g) than in non-stunted children (1.90 g). Dietary diversity levels were lower among stunted children than non-stunted children. In conclusion, daily total protein and animal protein intakes from CF among stunted children were lower, and their dietary diversity was less compared to non-stunted children. Nutrition programs are recommended to promote protein-rich, diverse, and appropriately portioned CF for stunted children to support their growth and development.